The spectrum of structural and functional imaging abnormalities in temporal lobe epilepsy. Issue 1 (9th June 2016) - Bernhardt, Boris C.; Bernasconi, Andrea; Liu, Min; Hong, Seok‐Jun; Caldairou, Benoit; Goubran, Maged; Guiot, Marie C.; Hall, Jeff; Bernasconi, Neda
Abstract : Objective: Although most temporal lobe epilepsy (TLE) patients show marked hippocampal sclerosis (HS) upon pathological examination, 40% present with no significant cell loss but gliotic changes only. To evaluate effects of hippocampal pathology on brain structure and functional networks, we aimed at dissociating multimodal magnetic resonance imaging (MRI) characteristics in patients with HS (TLE‐HS) and those with gliosis only (TLE‐G). Methods: In 20 TLE‐HS, 19 TLE‐G, and 25 healthy controls, we carried out a novel MRI‐based hippocampal subfield surface analysis that integrated volume, T2 signal intensity, and diffusion markers with seed‐based hippocampal functional connectivity. Results: Compared to controls, TLE‐HS presented with marked ipsilateral atrophy, T2 hyperintensity, and mean diffusivity increases across all subfields, whereas TLE‐G presented with dentate gyrus hypertrophy, focal increases in T2 intensity and mean diffusivity. Multivariate assessment confirmed a more marked ipsilateral load of anomalies across all subfields in TLE‐HS, whereas anomalies in TLE‐G were restricted to the subiculum. A between‐cohort dissociation was independently suggested by resting‐state functional connectivity analysis, revealing marked hippocampal decoupling from anterior and posterior default mode hubs in TLE‐HS, whereas TLE‐G did not differ from controls. Back‐projection connectivity analysis from cortical targets revealed consistently decreased network embedding across all subfields in TLE‐HS, while changes in TLE‐G were limited to the subiculum. Hippocampal disconnectivity strongly correlated to T2 hyperintensity and marginally to atrophy. Interpretation: Multimodal MRI reveals diverging structural and functional connectivity profiles across the TLE spectrum. Pathology‐specific modulations of large‐scale functional brain networks lend novel evidence for a close interplay of structural and functional disruptions in focal epilepsy. Ann Neurol 2016;80:142–153